Opinion on open-science practices and the importance of scientists’ information literacy skills in context of open science at the university of Rijeka, Croatia – a cross-sectional study - Dejana Golenko; Evgenia Arh; Ksenija Bazdaric (European Science Editing, 2023)
Background: Although opinions of scientists about open access and the importance of their skills in information literacy have been investigated earlier but not, to our knowledge, of those in Croatia.Objective: The objective was to analyse the opinions on open access and on open-science practices before implementing open-science policies.Methods: Scientists at the University of Rijeka (N = 1256) were invited to complete, anonymously, an online questionnaire on open science (Google Forms) in 2020 and their responses were analysed.Results: Altogether 192 participants (a response rate 15%) were involved in this study, of which 110 (57%) were women. The mean age of the participants was 42 years (stand-ard deviation 11). The participants pursued careers in biomedical (37%), social (31%), or technical (14%) sciences; 20% were early-career researchers or postdoctoral research-ers, and 80% held the rank of assistant professor or higher. Most of them (88%) agreed that journals should be open access and 77% said they would choose the open-access journal if they had to choose between two journals with similar impact factors. Most (83%) considered publishing fees (article processing charges) to be too high; fewer than half (45%) considered the impact factor to be more important than open access; and 28% believed open access journals to be of lower quality. Nearly three-fourths (74%) had published at least one article in an open access journal, and 45%, without paying any fee. Only a few (10.9%) archived their articles in institutional or national repositories; more than a quarter (27%), on their web pages; and close to half (43%), on their social networks. To obtain papers not available to read online, more than half (56%) used Sci-Hub; slightly more than half (51%) wrote to the authors; 40% asked col-leagues for help; and 35% approached a librarian.Conclusions: Most of the scientists in our study were in favour of open access but con-sidered the publication fees to be too high. Their archiving was inadequate: few used any institutional or national repositories. Therefore, the scientists need to be more information literate and require guidance and help from librarians and will benefit from training in information literacy including the principles of open access.